2011
DOI: 10.1007/s00415-011-6247-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation of stroke

Abstract: Despite ongoing improvements in the acute treatment of cerebrovascular diseases and organization of stroke services, many stroke survivors are in need of neurorehabilitation, as more than two-thirds show persisting neurologic deficits. While early elements of neurorehabilitation are already taking place on the stroke unit, after the acute treatment, the patient with relevant neurologic deficits usually takes part in an organized inpatient multidisciplinary rehabilitation program and eventually continues with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 127 publications
0
42
0
2
Order By: Relevance
“…Stroke is a health concern worldwide and one of the main causes of disability (Kolominsky-Rabas et al, 2001;Albert and Kesselring, 2012). Motor impairment is the main cause of disability after stroke, leading to major health problems (Boggio et al, 2007;Clarke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a health concern worldwide and one of the main causes of disability (Kolominsky-Rabas et al, 2001;Albert and Kesselring, 2012). Motor impairment is the main cause of disability after stroke, leading to major health problems (Boggio et al, 2007;Clarke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review concluded that spasticity develops in 20%Y25% of all patients with firstever stroke and in 27%Y43% of those with paresis 1Y18 mos after stroke. 6 Upper-limb spasticity has been found to influence the functional abilities of the upper-limbs 12 and, therefore, also the rehabilitation process.…”
mentioning
confidence: 99%
“…Spasticity is considered to be the important factor hampering patients' functional recovery, especially in the upper limbs, even if multiple neurorehabilitation techniques were conducted [11,12]. For instance, bilateral arm training, one of the active neurorehabilitation treatments, shows less effectiveness when being compared with other treatments [13].…”
Section: Discussionmentioning
confidence: 99%